2017
DOI: 10.1002/ctpp.201700109
|View full text |Cite
|
Sign up to set email alerts
|

Ion potential in non‐ideal dense quantum plasmas

Abstract: The screened ion potential in non‐ideal dense quantum plasmas is investigated by invoking the Singwi–Tosi–Land–Sjölander approximation for the electronic local field correction at densities rs ≲ 2 and degeneracy parameters θ ≲ 1, where rs is the ratio of the mean inter‐particle distance to the first Bohr radius, and θ is the ratio of the thermal energy to the Fermi energy of the electrons. Various cross‐checks with ion potentials obtained from ground‐state quantum Monte Carlo data, the random phase approximati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…[ 37 ] This negative minimum, leading to an attraction between like charged ions, fades with the increase in θ , that is, the temperature of electrons. We note that this behaviour of the STLS potential and parameters where it is applicable have been recently discussed by Moldabekov et al [ 30,37 ] At r s = 4 and θ = 0.5, the QMC potential also develops a very shallow negative minimum at r ≃ 4.5 a B < r 0 = 7.8 a B , which is beyond the weak electron‐ion coupling distance, meaning that this result also has to be discarded as a possible artefact of linear response theory. Therefore, even though an exact result for the electronic density response function in the linear response approximation is being used, the screened potential computed using linear response theory can lead to an unphysical ion‐ion attraction at sufficiently large r s and small θ (see also Dornheim et al [ 21 ] for a first investigation of nonlinear effects of electrons at WDM conditions).…”
Section: Numerical Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…[ 37 ] This negative minimum, leading to an attraction between like charged ions, fades with the increase in θ , that is, the temperature of electrons. We note that this behaviour of the STLS potential and parameters where it is applicable have been recently discussed by Moldabekov et al [ 30,37 ] At r s = 4 and θ = 0.5, the QMC potential also develops a very shallow negative minimum at r ≃ 4.5 a B < r 0 = 7.8 a B , which is beyond the weak electron‐ion coupling distance, meaning that this result also has to be discarded as a possible artefact of linear response theory. Therefore, even though an exact result for the electronic density response function in the linear response approximation is being used, the screened potential computed using linear response theory can lead to an unphysical ion‐ion attraction at sufficiently large r s and small θ (see also Dornheim et al [ 21 ] for a first investigation of nonlinear effects of electrons at WDM conditions).…”
Section: Numerical Resultssupporting
confidence: 70%
“…The advancement of WDM and ICF research has sparked high interest in the study of screening phenomena at partially and weakly degenerate cases. [ 28–34 ] In this regime, the analytic formulas for the screened potentials were discussed using the long wavelength approximation and often neglected exchange‐correlations effects. [ 28,29,31,35,36 ] Moldabekov et al have analysed various analytical models and the quality of the long wavelength approximation in the WDM regime by comparing them to the random phase approximation (RPA) result [ 31,37 ] computed without taking the long wavelength limit as well as to data obtained taking into account electronic exchange correlation effects both in the finite temperature Singwi–Tosi–Land–Sjölander (STLS) approximation [ 38 ] and using ground‐state QMC data [ 39–41 ] for the local field correction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the temperature equilibration in dense plasmas needs further study, implementing more involved theories for the description of the screening (e.g., see Ref. []).…”
Section: Resultsmentioning
confidence: 99%
“…In a nutshell, it was shown that nonlinear effects can indeed become important in many situations that are of relevance to contemporary experiments, for example with free-electron lasers [44,45]. Moreover, Moldabekov et al [46,47] have shown that at r s ≥ 4 the screened ion potential computed in LRT exhibits a negative minimum which can lead to an effective ion-ion attraction. However, this could be an artifact of LRT, and might vanish when nonlinear effects are properly taken into account.…”
mentioning
confidence: 99%